Rate of Hypokalemia and Risk Factors in Patients on Peritoneal Dialysis Under PD First Policy (Medico Legal Update, 2021)
Background: Hypokalemia is common among peritoneal dialysis (PD) patients. The incidence rate ofhypokalemia and risk factors were investigated.Material and Method: A retrospective cohort, enrolled 1,044 incident PD patients under the Universal HealthCoverage(UHC) Scheme of a regional hospital between January 2012 and December 2018. Hypokalemiawas defined as having serum potassium less than 3.5mEq/L. The rate of hypokalemia in episodes per oneyear at risk was determined. Risk factors of hypokalemia were reported as an incidence rate ratio usingPoisson regression.Results: The incidence rate of hypokalemia was 2.21(95% confidence interval, 2.14-2.27)episodes per oneyear at risk. Risk factors of hypokalemia were ; older than 60 years, female, diabetes, bodyweight less than45 kg, serum albumin less than 3.5 g/dL, serum phosphate less than 2.5 mg/dL, and total lymphocyte countless than 1,500 cells/mm3.Conclusions: Hypokalemia was frequently occurred in PD patients. Elderly PD patients, female, diabetes,malnutrition, low serum albumin, and lowserum phosphate had higher risks to develop hypokalemia.